Entre saberes e sabores: ações formativas em educação linguística e saberes docentes mediadas pelo professor coordenador - Domingos, Joice (2016)
The present work presents a survey about knowledge teachers, based on the studies conducted by Tardif and Freire. These are mobilized by teachers in their teaching practice. Justified the relevance of this research, since the teacher as a critical intellectual and transforming of your practice knowledge, which are learned throughout initial training and through the educational practice carried out in the classroom. This study also discusses Educational Linguistics, presenting a concept based on Passarelli and Palma and Turazza, returning to the concept presented by Bechara - teaching the maternal laguage in order to make the student in learner-teaching being - in a polyglot of their own language, or is, someone who can adapt his speech to several communicative situations, overcoming a language school that desmitifique the default rule, this which in turn is considered as the only prestigious worthy. The survey also proposes possible actions training / guidance mediated by Professor Educational Coordinator within a perspective of knowledge and Linguistic Education